Secular Republic and the Old Order - Mustafa Kemal Atatürk and Turkish identity - Sulkowski, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mustafa Kemal Atatürk continues to stand firm as a major symbol of the Turkish republicanism, though there is little doubt that Turkey today undergoes deep transformation in the sphere of the relations between politics and religion. As Bernard Lewis explains, the Ottoman Turks identified with Islam so profoundly that they in fact submerged their identity in Islam.
Keywords: Turkey; laicism; islamization; Atatürk, Mustafa Kemal (prezydent Turcji; 1881-1938)